Characterization of phenylalanine ammonia-lyase genes facilitating flavonoid biosynthesis from two species of medicinal plant Anoectochilus - Lin Yang; Wan-Chen Li; Feng-ling Fu; Jingtao Qu; Fuai Sun; Haoqiang Yu; Juncheng Zhang (PeerJ, 2022)
Background Anoectochilus roxburghii and Anoectochilus formosanus, belong to the Anoectochilus genus, have been used for Chinese herbal drugs as well as health food. Phenylalanine ammonia-lyase (PAL), the key enzyme in primary metabolism and phenylpropanoid metabolism, produces secondary metabolites (flavonoids) in plants, which are beneficial for the biosynthesis of phenylpropanoid metabolites. Methods The PAL genes were cloned from A. formosanus and A. roxburghii according to our previous transcriptomic analysis. The PALs were introduced into pCAMBIA2300-35S-PAL-eGFP to generate 35S-PAL-eGFP. The constructs were further used for subcellular localization and transgenic Arabidopsis. The expression of AfPAL and ArPAL under precursor substance (L-Phe), NaCl, UV, and red-light were analyzed by real-time quantitative PCR (RT-qPCR). Results AfPAL and ArPAL , encoding 2,148 base pairs, were cloned from A. formosanus and A. roxburghii. The subcellular localization showed that the ArPAL and AfPAL were both localized in the nucleus with GPF. Quantitative RT-PCR analysis indicated that the ArPAL and AfPAL genes function in the phenylalanine pathway as well as response to induced conditions. Overexpression of the AfPAL and ArPAL could increase flavonoids and anthocyanin content in the transgenic Arabidopsis. Discussion The results suggest that AfPAL and ArPAL play a crucial role in the flavonoid biosynthesis in Anoectochilus. Also, our study provides new insights into the enrichment of secondary metabolites of traditional Chinese medicines A. formosanus and A. roxburghii, which can improve their medicinal active ingredients and be used for drug discovery in plants.